Alternative Virtual Lab-Based Practical Learning Model to Improve Scientific Attitude and Science Process Skills - Tawil, Muh.; Rusli, Muh. Aqil; Bakkara, Hasanuddin; Jatmiko, Budi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
A virtual laboratory is computer software that has the ability to perform mathematical modeling of computer devices presented in the form of simulations. Virtual laboratories are not a substitute for real laboratories, but are used to complement and improve the weaknesses of real laboratories. This research aims to determine the effect of virtual labs on science education students' scientific attitude abilities and science process skills in science courses. The design of this research is a repeated pre-experiment without a control class, with a one-group and pretest-posttest design. The sample in this study was 60 students of the science education study program at Makassar State University, Indonesia, used as experiment 1 group A (n = 30), experiment 2 group B (n = 30). Two groups (experiment 1 and experiment 2) were tested with a pretest and posttest. Each group uses a virtual lab-based practical model (PbVLab). Scientific attitudes and scientific skills were measured using multiple choice tests before and after treatment. The mixed method ANOVA statistical test was used to determine how effective the use of PbVLab was in improving scientific attitudes and science process skills. The results of testing research based on Within-Subjects Effects showed that there was no difference between the pretest-posttest scores for scientific attitudes and scientific skills (F = 0.00; p < 0.05) in each group. The results of the pairwise comparison showed a significance value of <0.05, and there was a significant increase in the pretest-posttest scores for scientific attitudes and science process skills in each group. The effect size results (partial eta squared) show that experimental group 1 experienced an increase in scientific attitudes by 52%; science process skills 53%, experimental group 2 scientific attitudes 54% and science process skills 56%. So, it can be concluded that experimental group 1 and experimental group 2 (PbVab model) provide the most effective contribution to improving scientific attitudes and science process skills.